2017
DOI: 10.1007/s10336-016-1422-7
|View full text |Cite
|
Sign up to set email alerts
|

Unusual incubation behavior and embryonic tolerance of hypothermia in the Sichuan Partridge (Arborophila rufipectus)

Abstract: Incubation is an energetically demanding phase of avian reproduction. Single-sex incubators are often faced with a direct conflict between incubation and foraging. We report an unusual incubation behavior of the Sichuan Partridge (Arborophila rufipectus), with long recesses of females and embryonic hypothermia, at Laojunshan National Nature Reserve, southwest China. The Sichuan Partridge is a globally endangered species that inhabits subtropical evergreen and deciduous broadleaf forests at 1100-2250 m a.s.l. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Nest attentiveness estimates were lower (84%) relative to other ground‐nesting galliforms, including Greater Sage‐Grouse (96%; Centrocercus urophasianus ), Greater Prairie‐Chicken (95% Tympanuchus cupido ), and White‐tailed Ptarmigan (95%; Lagopus leucura ; Wiebe & Martin, , Deeming, , Coates & Delehanty, , Winder et al, ). However, our estimates of nest attentiveness were similar to other related species such as the Sichuan Partridge (82%, Arborophila rufipectus ) and Blood Pheasant (72%, Ithaginis cruentus ; Fu et al, ; Jia et al, ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Nest attentiveness estimates were lower (84%) relative to other ground‐nesting galliforms, including Greater Sage‐Grouse (96%; Centrocercus urophasianus ), Greater Prairie‐Chicken (95% Tympanuchus cupido ), and White‐tailed Ptarmigan (95%; Lagopus leucura ; Wiebe & Martin, , Deeming, , Coates & Delehanty, , Winder et al, ). However, our estimates of nest attentiveness were similar to other related species such as the Sichuan Partridge (82%, Arborophila rufipectus ) and Blood Pheasant (72%, Ithaginis cruentus ; Fu et al, ; Jia et al, ).…”
Section: Discussionsupporting
confidence: 84%
“…Incubation recesses are directional movements made away from nesting locations during active incubation, which are thought to allow individual's time to acquire necessary resources (Deeming, ) while maintaining appropriate egg temperatures (Deeming, ; Fu et al, ; Jia, Sun, & Swenson, ; Naylor, Szuba, & Bendell, ; Webb, ). However, movements associated with recesses may increase predation risk to both the female and nest (Martin, ), and therefore, the distribution of resources within an accessible landscape during incubation should drive frequency and distance of individual recess movements (Conley et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…During periods of rainfall the nest is likely to lose heat via increased conductance through damp nesting materials (Reid et al, 2002;Hilton et al, 2004;Heenan, 2013), so our result may indicate that larger clutches buffer the effects of rainfall because a smaller clutch surface area to volume ratio reduces exposure to damp nesting materials or humid and cold air. However, it is also important to consider the potential impact of weather on the behavior of incubating birds; for example, any effects of increased conductance may be confounded by females adjusting their nest attentiveness during periods of heavy rainfall and storms (MacDonald et al, 2013;Fu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The altitude of Laojunshan National Nature Reserve ranges from 1100 to 2008 m and has an annual average temperature of 12.5 °C [4]. Previous studies reported that Sichuan partridge eggs experienced an average of 4.2 h per day below 26 °C (the ‘Physiological Zero Temperature’) at which the embryo cannot develop [47]. Although the temperature is fairly more than that reported for most birds and likely to cause death of the embryo, the hatching success of Sichuan partridge was 88.4%, which is approaching the average hatchability rate for birds generally (89.1%) [47].…”
Section: Discussionmentioning
confidence: 99%